A Faculty-Based Mentorship Circle: Positioning New Faculty for Success - Waddell, Janice; Martin, Jennifer; Schwind, Jasna; Lapum, Jennifer (Canadian Journal of Higher Education, 2017)
Multiple and competing priorities within a dynamic and changing academic environment can pose significant challenges for new faculty. Mentorship has been identified as an important strategy to help socialize new faculty to their roles and the expectations of the academic environment. It also helps them learn new skills that will position them to be successful in their academic career. In this article, the authors report on the implementation and evaluation of a mentorship circle initiative aimed at supporting new faculty in the first two years of their academic appointment. Participants reported that the mentorship circle provided them with a culture of support, a sense of belonging, and a safe space to discuss concerns and learn strategies from both mentors and fellow mentees as they adjusted to their new position. The interdisciplinary nature of the mentorship circle further facilitated faculty members’ capacity to navigate their role as new faculty and foster colleagueship.